DELLA1-Mediated Gibberellin Signaling Regulates Cytokinin-Dependent Symbiotic Nodulation. Issue 4 (18th October 2017) - Fonouni-Farde, Camille; Kisiala, Anna; Brault, Mathias; Emery, R.J. Neil; Diet, Anouck; Frugier, Florian
Abstract : DELLA1-mediated GA signaling interplays with the CRE1-dependent cytokinin pathway to regulate symbiotic nodulation in the Medicago truncatula model legume. Abstract: In legume plants, low-nitrogen soils promote symbiotic interactions with rhizobial bacteria, leading to the formation of nitrogen-fixing root nodules. Among critical signals regulating this developmental process are bacterial Nod Factors (NFs) and several plant hormones, including cytokinins (CKs) and gibberellins (GAs). Here, we show in Medicago truncatula that GA signaling mediated by DELLA1 decreases the amount of bioactive CKs in roots and negatively impacts the Cytokinin Response1 (CRE1)-dependent NF activation of a subset of CK-signaling genes as well as of the CK-regulated Nodulation Signaling Pathway2 and Ethylene Response Factor Required for Nodulation1 early nodulation genes. Consistently, a dominant-active DELLA1 protein can partially rescue the reduced nodulation of the cre1 mutant and triggers the formation of nodule-like structures when expressed in the root cortex or in the root epidermis. This suggests a model where the DELLA1-mediated GA signaling interplays with the CRE1-dependent CK pathway to regulate early nodulation in response to both NF and CK signals critical for this symbiotic interaction.